Stalinism for All Seasons : A Political History of Romanian Communism - Tismaneanu, Vladimir (Book collections on Project MUSE., 2003)
Stalinism for All Seasons is the first comprehensive history of the Romanian Communist Party (RCP). It traces the origins of the once-tiny, clandestine revolutionary organization in the 1920s through the years of national power from 1944 to 1989 to the post-1989 metamorphoses of its members. Vladimir Tismaneanu uses documents that he discovered while working in the RCP archives in Bucharest in the mid-1990s and interviews with many of the party members from the Ceau_escu and Gheorghiu-Dej eras to tell the absorbing story of how RCP members came to power as exponents of Moscow and succeeded in.